Measurements and analysis of different front-end configurations for monolithic SiGe BiCMOS pixel detectors for HEP applications. (22nd December 2021) - Martinelli, F.; Magliocca, C.; Cardella, R.; Charbon, E.; Iacobucci, G.; Nessi, M.; Paolozzi, L.; Rücker, H.; Valerio, P.
Abstract: This paper presents a small-area monolithic pixel detector ASIC designed in 130 nm SiGe BiCMOS technology for the upgrade of the pre-shower detector of the FASER experiment at CERN. The purpose of this prototype is to study the integration of fast front-end electronics inside the sensitive area of the pixels and to identify the configuration that could satisfy at best the specifications of the experiment. Self-induced noise, instabilities and cross-talk were minimised to cope with the several challenges associated to the integration of pre-amplifiers and discriminators inside the pixels. The methodology used in the characterisation and the design choices will also be described. Two of the variants studied here will be implemented in the pre-production ASIC of the FASER experiment pre-shower for further tests.